Mechanical Models of Habits and Aesthetic Perception in Descartes and Gassendi - Gasparri, Giuliano (Aisthesis, 2024)
The early modern age saw an increasing use of mechanical models in order to explain sense perception, imagination, emotions, memory, and habit. René Descartes and Pierre Gassendi tried to innovate music theory in the light of such models. Thus, the bodily mechanism of habits accounts for the skill in playing music, singing, and dancing, but also – to a certain extent – for the perception of beauty and the shaping of taste.